Introductory remarks on Serbian-Slovak cultural ties since the 19th century to the present, basic outline - Perný, Lukáš (Napredak, 2026)
The proto-study outlines the basic contours of Serbian–Slovak cultural relations from the 19th cen tury to the present. It traces the genealogy of reciprocity from the idea of Slavic cooperation, represented by figures such as Ján Kollár, Pavel Jozef Šafárik, and Svetozar Miletić, through Czechoslovak–Yugoslav relations in the 20th century, to contemporary forms of exchange. It places particular focus on parallels and cultural contacts, the role of Slovaks in Vojvodina, and the activities of contemporary actors. The text emphasizes the importance of cultural cooperation as a perspective for the further development of relations in the 21st century.